The Intelectual's Constribution In The National Movement Of In Indonesian 1908-1928 - Dwi Nur Imsawati; Sri Handayani; Sumardi Sumardi (JURNAL HISTORICA, 2017)
Intellectual is Indonesian youths who are educated and fight for his nation. Intelectual’s brought a new way struggle of Indonesian nation which no longer rely on physical but on ability and intellectual. Emerging of national movement pioneered by intellectual who have got Dutch colonial government's education. The problems in this research are the factors behind the emerging of the intellectual and the contribution of the learned classes in the national movement of Indonesia. This research aims to describe about the role of intellectual in the national movement of Indonesia on 1908-1928. This research method uses historical research method, which consists of four steps: heuristics, criticism, interpretation and historiography. The benefits of this research to increase knowledge and can be used as a reference for the next research. The conclusion that can be drawn from this research is the first factor that is the background of intellectual emerging is the implementation of ethical politics policy and the implementation of Dutch colonial education in Indonesia. The Dutch government provides opportunities for the people of Indonesia to obtain an education. Second, intellectual's contribution in the national movement of Indonesia which include education sector, economic sector, social sector and emerging of national awareness for nation and state. Keywords: Contribution, Intelectual, National Movement